(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Pedagogical culture plays a crucial role in the professional development of teachers and the quality of education they provide. This article explores the mechanisms underlying the development of pedagogical culture among teachers in general education schools. It examines various factors, including continuous professional development, collaborative learning environments, mentoring programs, and organizational support, that contribute to the enhancement of pedagogical culture. Understanding these mechanisms is essential for educational policymakers, school administrators, and teacher trainers to design effective strategies for cultivating a strong pedagogical culture in schools.